Pengaruh Penerapan Media Assemblr Edu terhadap Hasil Belajar IPA Kelas VIII SMPN 2 Pattallassang Kabupaten Gowa - Nurul Azizah; Muhammad Nawir; Akram (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aimed to determine the effect of implementing Assemblr Edu media on science learning outcomes of eighth-grade students at SMPN 2 Pattallassang, Gowa Regency. This study employed a quantitative approach using a pre-experimental method with a One Group Pretest–Posttest Design. The sample consisted of 31 students selected through purposive sampling. Data were collected through observation, tests, and documentation. The data were analyzed using descriptive and inferential statistical analysis. The results showed an improvement in students’ learning outcomes after the implementation of Assemblr Edu media. The average pretest score increased from 65 to 88 in the posttest. In addition, students’ learning activities improved during the learning process. The findings indicate that the implementation of Assemblr Edu media had a positive effect on science learning outcomes of eighth-grade students at SMPN 2 Pattallassang, Gowa Regency.